Enhancing Ionic Conductivity and Stability of Electrolyte Membranes: A Study on CQD-GO Composites for Aluminum-Air Batteries - Ezi Puspita Dewi; Ridwan, Firman; Agusto , Dean Bilalwa; Wismalqi; Gusriwandi (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
The development of efficient and sustainable energy storage technologies is crucial to address the depletion of fossil fuels and environmental pollution. This study focuses on the synthesis and characterization of a novel electrolyte membrane based on the integration of Carbon Quantum Dots (CQDs) derived from coconut-shell charcoal into a Graphene Oxide (GO) matrix for application in aluminum-air batteries. The CQDs were synthesized using a simple, low-cost, and environmentally friendly hydrothermal method, whereas the GO-based membrane was prepared via a solution casting technique. The physical and electrochemical properties of the resulting CQD-GO composite membranes were systematically investigated using various characterization techniques, including Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Electrochemical Impedance Spectroscopy (EIS), and Scanning Electron Microscopy (SEM). The results revealed that the incorporation of CQDs significantly enhanced the ionic conductivity, reduced the internal resistance, and improved the interfacial stability of the membrane compared with pristine GO. The synergistic effect between the CQDs and GO was attributed to the formation of hybrid conductive pathways and the enhanced ion mobility within the membrane structure. Furthermore, the CQD-GO membrane exhibited excellent stability in the electrochemical environment typically encountered in aluminum-air batteries. These findings highlight the potential of integrating biomass-derived CQDs with GO to develop high-performance electrolyte membranes for advanced energy storage applications, paving the way for more efficient and environmentally friendly aluminum-air batteries.